Laser triggered Z-pinch broadband extreme ultraviolet source for metrology - Lunney, James; Tobin, David (My University, 2013)
We compare the extreme ultraviolet emission characteristics of tin and galinstan (atomic %: Ga: 78.35, In: 14.93, Sn: 6.72) between 10 nm and 18 nm in a laser-triggered discharge between liquid metal-coated electrodes. Over this wavelength range, the energy conversion efficiency for galinstan is approximately half that of tin, but the spectrum is less strongly peaked in the 13?15 nm region. The extreme ultraviolet source dimensions were 110625 lm diameter and 5006125 lm length. The flatter spectrum, and 19 C melting point, makes this galinstan discharge a relatively simple high radiance extreme ultraviolet light source for metrology and scientific applications.
PUBLISHED
Keywords: ultraviolet; ultraviolet